AB0827 IMPACT OF BASELINE BODY MASS INDEX ON THE EFFICACY AND SAFETY OF TOFACITINIB IN PATIENTS WITH PSORIATIC ARTHRITIS. (2nd June 2020) - Ritchlin, C. T.; Ogdie, A.; Giles, J. T.; Gomez-Reino, J. J.; Helliwell, P.; Stockert, L.; Young, P.; Joseph, W.; Mundayat, R.; Graham, D.; Woolcott, J.; Romero, A. B.
Abstract : Background: Obesity is highly prevalent in PsA ( 45%) 1 and is associated with a reduced response to TNF inhibitors. 2 Tofacitinib is an oral Janus kinase inhibitor for the treatment of PsA. Objectives: This post hoc analysis assessed tofacitinib efficacy and safety in patients (pts) with PsA by baseline (BL) body mass index (BMI) category. Methods: Data were pooled from two placebo (PBO)-controlled, double-blind, Phase 3 studies in pts with active PsA and an inadequate response to ≥1 conventional synthetic DMARD (OPAL Broaden [12 months; NCT01877668 ]) or to ≥1 TNF inhibitor (OPAL Beyond [6 months; NCT01882439 ]). 3, 4 This analysis included pts randomised to tofacitinib 5 mg twice daily (BID), tofacitinib 10 mg BID or PBO, stratified by BL BMI: <25 kg/m 2, ≥25–<30 kg/m 2, ≥30–<35 kg/m 2, or ≥35 kg/m 2 . Efficacy and safety were reported to Month (M)3. M3 efficacy outcomes included ACR20/50/70 and HAQ-DI responses, dactylitis and enthesitis resolution rates and changes from BL in HAQ-DI, Short Form-36 Version 2 (SF-36v2) Physical (PCS) and Mental Component Summary (MCS) scores, and Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) scores. Safety outcomes included adverse events (AEs), such as cardiovascular (CV) events and changes in lipid levels and liver function tests (LFTs). Results: This analysis included 710 pts; 43.8% were obese (BMI ≥30). At BL, 161 (22.7%) pts had a BMI <25, 238 (33.5%) had a BMI ≥25–<30, 186 (26.2%) had a BMI ≥30–<35 and 125 (17.6%) had a BMI ≥35. Most pts were white (92.5–96.8%), middle-aged (mean: 44.5–51.2 yrs) and female (49.5–65.6%). Greater proportions of obese pts were from Russia/Eastern Europe (35.0%) and USA/Canada (31.8%), vs the rest of world. At BL, higher BMI correlated with an increased prevalence of metabolic syndrome (4.3% in BMI <25 to 76.0% in BMI ≥35) and CRP levels >2.87 mg/L (49.1% in BMI <25 to 84.0% in BMI ≥35). Higher proportions of pts (42.5–47.9%) in BL BMI categories <35 reported no prior biologic DMARD use, vs pts with a BL BMI ≥35 (33.6%). At M3, efficacy improvements were greater in tofacitinib-treated pts vs PBO-treated pts (Figure 1 ). In pts with a BL BMI ≥35, a trend towards fewer pts responding was observed (Figure 1 ) and mean changes from baseline in SF-36v2 PCS and MCS and FACIT-F generally appeared lower (Figure 2 ) vs pts in lower BL BMI categories. Up to M3, the proportions of pts with AEs, and percentage change from BL in lipid levels and LFTs, were generally similar across all BL BMI categories. Three CV events were reported: non-fatal cerebrovascular accident, transient ischemic attack (both tofacitinib 5 mg BID, BMI ≥30–<35) and coronary artery revascularisation (PBO; BMI ≥35). Limitations include the 3-month observation time, particularly for safety findings, thus longer observation times are warranted. Conclusion: Regardless of BL BMI, tofacitinib demonstrated greater efficacy than PBO at M3 in pts with PsA. Similar to other advanced therapies, 2 reduced efficacy was generally observed in tofacitinib and PBO pts with a BL BMI ≥35. Tofacitinib safety appeared consistent across all BL BMI categories. References: [1]Labitigan et al. Arthritis Care Res (Hoboken) 2014;66:600-07. [2]Singh et al. PLoS One 2018;13:e0195123. [3]Mease et al. NEJM 2017;377:1537-50. [4]Gladman et al. NEJM 2017;377:1525-36. Acknowledgments: Medical writing support was provided by Mark Bennett of CMC Connect, McCann Health Medical Communications, and funded by Pfizer Inc. Disclosure of Interests: Christopher T. Ritchlin Grant/research support from: UCB Pharma, AbbVie, Amgen, Consultant of: UCB Pharma, Amgen, AbbVie, Lilly, Pfizer, Novartis, Gilead, Janssen, Alexis Ogdie Shareholder of: Amgen, Novartis, Pfizer Inc, Grant/research support from: Novartis, Consultant of: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly, Novartis, Pfizer Inc, Jon T Giles Grant/research support from: Pfizer Inc, Juan Jesus Gomez-Reino Grant/research support from: AbbVie, Novartis, Pfizer Inc, Roche, UCB, Consultant of: Pfizer Inc, Speakers bureau: AbbVie, Bristol-Myers Squibb, Janssen, MSD, Pfizer Inc, Roche, UCB, Philip Helliwell: None declared, Lori Stockert Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Pamela Young Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Wael Joseph Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Rajiv Mundayat Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Daniela Graham Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, John Woolcott Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Ana Belen Romero Shareholder of: Pfizer Inc, Employee of: Pfizer Inc